PENERAPAN MANAJEMEN STRESS SEBAGAI TERAPI KOMPLEMENTER BAGI PENYINTAS KANKER DI KOMUNITAS KANKER INDONESIA (Jurnal Bakti Masyarakat Indonesia, 2021)
Cancer was a chronic and deadly disease in the world. A long period of cancer treatment effect the psychological of cancer patients, particularly stress. One of the complementary or non-pharmacological therapy for cancer is stress management. This community service activity aims to provide stress management as a complementary therapy for cancer patients to decrease stress levels. We conducted progressive muscle relaxation and guided imagery. This activity is carried out in 1 time (one meeting) and took place in the Indonesian Cancer Care Community (ICCC) and involved 15 cancer survivors and warriors. The media used in this activity are PPT and zoom meeting platform. They submitted pre and post-test, which were analyzed with Paired t-test. This study showed a different mean score of stress level between before and after stress management (Sig. 2 tailed